STRATEGI DAN PERAN PENDIDIKAN JASMANI DAN OLAHRAGA DALAM MEMBENTUK KARAKTER ANAK BANGSA - Rian Andriansyah; M. Naufal Dzaky Immamughni Alwasi; Fauzan Amrullah Ramadhan; Elsa Zahra; Dwi Muhammad Riski (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Education is a key element in improving the quality of human resources in the world. When the quality of human resources increases, life on earth will be better, which in turn encourages high productivity. Conversely, if the quality of human resources decreases, life on earth will also decline. The method used is a qualitative research method with a type of literature review, namely a review of research results and books on existing concepts to be studied in depth with a qualitative approach analysis so as to find new knowledge that can be used in the future. The results of the study are Physical education and sports provide various benefits, including physical health which can reduce the risk of chronic diseases, social development through interaction in time. Character education basically aims to form individuals who have integrity, empathy, a sense of responsibility for themselves and society, and a commitment to upholding truth and justice. Physical activity in physical education also plays an important role in reducing stress and anxiety levels.